The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1038/sj.leu.2404192
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathogenesis of MALT lymphoma: two signaling pathways underlying the antiapoptotic effect of API2-MALT1 fusion protein

Abstract: At least three recurrent chromosomal translocations, t(11;18)(q21;q21), t(1;14)(p22;q32), t(14;18)(q32;q21), involving the API2-MALT1 fusion protein, BCL10 and MALT1, have been implicated in the pathogenesis of mucosa-associated lymphoid tissue (MALT) lymphoma. Several lines of evidence indicated that both BCL10 and MALT1 are required for nuclear factor kappa B (NF-jB) activation by antigen receptor stimulation in lymphocytes, and API2-MALT1 can bypass this BCL10/MALT1 signaling pathway. Nuclear factor kappa B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 110 publications
1
9
0
1
Order By: Relevance
“…Apart from the t(11;18)(q21;q21) and t(1;14)(p22;q32) translocations, t(14;18)/IGH-MALT1, involving the MALT1 and IGH genes and resulting in the overexpression of MALT1, is the best-known and well-described translocation in MALT lymphomas (Sanchez-Izquierdo et al, 2003;Streubel et al, 2003). The translocation may deregulate MALT1, which would subsequently recruit and stabilize BCL10 and CARMA1 and trigger aberrant NFKB activation, thereby contributing to the proliferation of MALT lymphoma (Sanchez-Izquierdo et al, 2003;Streubel et al, 2003;Nakagawa et al, 2006). It occurs in some non-gastric MALT lymphoma originating from liver, lung, ocular adnexa, salivary gland, and skin (Streubel et al, 2004;Remstein et al, 2006;Palmedo et al, 2007) but only occasionally in gastric MALT lymphoma (Streubel et al, 2004;Remstein et al, 2006;Nakamura et al, 2007a).…”
Section: Discussionmentioning
confidence: 96%
“…Apart from the t(11;18)(q21;q21) and t(1;14)(p22;q32) translocations, t(14;18)/IGH-MALT1, involving the MALT1 and IGH genes and resulting in the overexpression of MALT1, is the best-known and well-described translocation in MALT lymphomas (Sanchez-Izquierdo et al, 2003;Streubel et al, 2003). The translocation may deregulate MALT1, which would subsequently recruit and stabilize BCL10 and CARMA1 and trigger aberrant NFKB activation, thereby contributing to the proliferation of MALT lymphoma (Sanchez-Izquierdo et al, 2003;Streubel et al, 2003;Nakagawa et al, 2006). It occurs in some non-gastric MALT lymphoma originating from liver, lung, ocular adnexa, salivary gland, and skin (Streubel et al, 2004;Remstein et al, 2006;Palmedo et al, 2007) but only occasionally in gastric MALT lymphoma (Streubel et al, 2004;Remstein et al, 2006;Nakamura et al, 2007a).…”
Section: Discussionmentioning
confidence: 96%
“…Certain chromosomal translocations, t(11;18) (q21;q21), t(1;14)(p22;q32), and t(14;18)(q32;q21), have been implicated in the pathogenesis of MZBCL, and it has been shown that these genetic aberrations utilize a common signaling pathway by ultimately targeting the same nuclear factor kappa B (NF-kB) signaling pathway (Lucas et al, 2001;Nakagawa et al, 2006). Ye et al (2003) reported that RT-PCR analysis identified the t(11;18)(q21;q21) in 16.3% of ocular adnexal MZBCL.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular genetics underlying the pathogenesis of MALT lymphoma are only recently being understood in detail for the three MALT-specific translocations t(11;18)/API2-MALT1, t(1;14)/IGH-BCL10, and t(14;18)/IGH-MALT1 (19). Antigen stimulation and CD40 triggering synergize in NF-nB activation through the formation of a CARMA1-BCL10-MALT1 ternary complex.…”
Section: Discussionmentioning
confidence: 99%
“…DNA of patients 1,4,18,19,20,22,26, and 28 was isolated from the fresh tumor samples using a High Pure PCR Template Preparation kit (Roche). The long-distance inverse PCR (LDI-PCR) for the joining and switch regions was done as described previously (9,10).…”
Section: Methodsmentioning
confidence: 99%